2010
DOI: 10.1530/eje-10-0284
|View full text |Cite
|
Sign up to set email alerts
|

Subjective health status in men and women with congenital adrenal hyperplasia: a population-based survey in Norway

Abstract: Background: Patients with classical congenital adrenal hyperplasia (CAH) require life-long corticosteroid therapy, with uncertain health outcome. Investigations of subjective health status in unselected populations of adult patients are needed. Objective: To identify all adult Norwegian patients with CAH and obtain population-based data on subjective and psychological health status, working ability and fertility. Patients, methods and design: Classical CAH patients were identified through search in electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 37 publications
5
74
2
6
Order By: Relevance
“…The glucocorticoid doses were also higher than the hydrocortisone doses of 15-25 mg/day suggested by the Endocrine Society (3). We previously reported that only 47% of the Norwegian patients use mineralocorticoid (17), which compared with 84% of the Swedish patients (32,33), which could contribute to the differences in both glucocorticoid doses and body composition. High blood pressure, including isolated diastolic hypertension, is, like fat mass, a marker of risk of cardiovascular disease (34).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The glucocorticoid doses were also higher than the hydrocortisone doses of 15-25 mg/day suggested by the Endocrine Society (3). We previously reported that only 47% of the Norwegian patients use mineralocorticoid (17), which compared with 84% of the Swedish patients (32,33), which could contribute to the differences in both glucocorticoid doses and body composition. High blood pressure, including isolated diastolic hypertension, is, like fat mass, a marker of risk of cardiovascular disease (34).…”
Section: Discussionmentioning
confidence: 96%
“…The patients were categorised as SW or SV, as defined by medical history and laboratory assessment (17), and the diagnosis was verified by genotyping of the CYP21A2 gene. The patients were assessed at four University Hospitals, according to a standardised protocol including measurements of height, weight, waist and hip circumference; supine blood pressure measurements; dual X-ray absorptiometry (DXA) with BMD and body composition.…”
Section: Subjects and Designmentioning
confidence: 99%
“…The burden and effect of these conditions on daily life, aspirations, and adaptation to the situation may cause impairments in physical, emotional, and social wellbeing. 27,28 Whether participants received psychological counseling did not affect their satisfaction with care, but unmet needs did. Psychosocial interventions should be limited to those who need and want such services.…”
Section: Discussionmentioning
confidence: 98%
“…In a Norwegian population-based survey, the subjective health status of adult 21-OHD patients was also impaired [17]. In a German cross-sectional study, we recently found in 81 adult 21-OHD patients mild impairment in HRQoL compared to healthy controls and the 21-OHD patients had better scores in the questionnaires than PAI patients [16].…”
Section: Discussionmentioning
confidence: 89%
“…Current data on HRQoL in adult patients with 21-OHD shows conflicting results [11][12][13][14], however the most recent studies showed impaired HRQoL also in 21-OHD patients [15][16][17].…”
mentioning
confidence: 97%